Rhenish Lignite – Energy Carrier and Versatile Raw Material through the Ages1. Issue 4 (14th May 2018) - Overhoff, Urs; Moser, Peter; Elsen, Reinhold; Vinzelberg, Gero; Eyll‐Vetter, Michael; Neuroth, Markus
Abstract: As Germany's most important, domestic fossil energy carrier, lignite plays a crucial role in electricity and heat production. Even though its share of the overall power production is decreasing due to a rising feed‐in from renewable energy sources, fossil energy carriers will go on providing base load and back‐up electricity in times when renewable energies are not able to produce enough electricity. Lignite and byproducts, which are gained during the conversion and exploitation of lignite, can be used for material utilization. The production of hydrocarbons or extraction of important raw materials are examples. It is expected, that this field of application will gain relevance in the future. Abstract : Lignite is the largest fossil mineral resource in Germany. Whereas at the start of the industrial use of lignite heat generation was in the fore, today the main area of application is the production of electricity. In future, however, the use of lignite as a base material to produce chemical feedstocks or fuels could also play a significant role.